High-quality colon cleansing and multiple neoplasia detection with 1L NER1006 versus mid-volume options: Post hoc analysis of phase 3 clinical trials - Epstein, Michael S.; Benamouzig, Robert; Halonen, Juha; Bisschops, Raf (Endoscopy International Open, 2020)
Background and study aims Multiple neoplasia increase the risk of colorectal cancer. High-quality cleansing may improve adenoma detection. We assessed whether a new bowel preparation can improve colon cleansing and multiple lesion detection.Patients and methods This post hoc analysis of two randomized clinical trials in Europe and the US assessed the per study and combined cleansing efficacy of overnight split dosing with (preparation + clear fluids) 1 + 1 L polyethylene glycol (PEG) NER1006 versus 2 + 1 L PEG + ascorbate (2LPEG) or 1 + 2 L oral sulfate solution (OSS) combined. Treatment-blinded central readers assessed cleansing quality using the Harefield Cleansing Scale (HCS). Patients with full segmental scoring were included. HCS segmental scores 0–4 (high-quality = HCS 3–4) were analyzed for NER1006 versus 2LPEG/OSS. Mean number of polyps or adenomas per patient (MPP/MAP) was calculated for treatments in patients with at least one polyp or adenoma.Results In 1037 patients, NER1006 attained a greater rate of HCS 3 scores (29 % vs. 20 %; P < 0.001) and HCS 4 scores (20 % vs. 17 %; P = 0.007) versus 2LPEG/OSS. More polyps (678 versus 585) and adenomas (397 versus 331) were detected with NER1006 (N = 517) versus 2LPEG/OSS (N = 520). In all neoplasia-positive patients, with increasing minimal per-patient neoplasia multiplicity from 1 to 10, NER1006 numerically improved MPP (difference ± SE: 0.48 ± 0.24 to 3.89 ± 3.37) and MAP (0.47 ± 0.26 to 7.50 ± 9.00) versus 2LPEG/OSS.Conclusions Low-volume NER1006 enhances high-quality cleansing versus medium-volume 2LPEG or OSS, individually and when combined. NER1006 may consequently facilitate the detection of multiple neoplasia in patients.